2012
DOI: 10.1002/ejoc.201200556
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Diphosphane‐ and NHC‐Containing Ruthenium Catalysts for the Catalytic Asymmetric Arylation of Aldimines with Organoboron Reagents

Abstract: For the first time, we report the application of [RuCl2(η6‐p‐cymene)]2 in the arylation of N‐activated aldimines with boronic acids and its derivatives to afford chiral amines, which are important intermediates in the syntheses of key bioactive compounds. The behavior of the chiral ligands, the imine substrates, and the organoboron reagents were studied. Very good enantioselectivities were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Asymmetric arylation of aldimines can afford such compounds, and the use of organoboron reagents as aryl donors is one of the most promising strategies for the synthesis of these compounds because of the stability, mild reactivity, and ease of handling of organoboron reagents . Since the first examples of asymmetric addition of arylboronic acids to aryl tosylimines catalyzed by chiral Rh complexes were reported in 2004, numerous efforts for the development of this type of reaction have focused on improving the catalytic activities and substrate diversity to include aliphatic imines and various types of protected aldimines. , As alternatives to Rh catalysis, other metals such as Pd and Ru catalyst systems were also investigated. Despite great advances in the development of this reaction, the catalysts have all been homogeneous metal complexes and less attention has been focused toward the development of heterogeneous catalysts.…”
mentioning
confidence: 99%
“…Asymmetric arylation of aldimines can afford such compounds, and the use of organoboron reagents as aryl donors is one of the most promising strategies for the synthesis of these compounds because of the stability, mild reactivity, and ease of handling of organoboron reagents . Since the first examples of asymmetric addition of arylboronic acids to aryl tosylimines catalyzed by chiral Rh complexes were reported in 2004, numerous efforts for the development of this type of reaction have focused on improving the catalytic activities and substrate diversity to include aliphatic imines and various types of protected aldimines. , As alternatives to Rh catalysis, other metals such as Pd and Ru catalyst systems were also investigated. Despite great advances in the development of this reaction, the catalysts have all been homogeneous metal complexes and less attention has been focused toward the development of heterogeneous catalysts.…”
mentioning
confidence: 99%
“…is required. As a first attempt, we switched to stronger NaOH as a base, that even when used in catalytic amounts (entry 8) incurred significant hydrolysis of the imine substrate ,. Gratifyingly, a catalytic amount of K 3 PO 4 (0.2 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the report here is the first that shows that a disulfoxide ligand system can be used in the 1,2‐addition reaction. A careful optimization study on the reaction conditions also led to a system where hydrolysis was not observed for the imine substrates,,, while mild reaction conditions in aqueous toluene were maintained giving high yields and enantioselectivities at catalyst loadings that are among the lowest reported…”
Section: Introductionmentioning
confidence: 99%
“…Due to our group's interest in the catalytic arylation of aldimine substrates, [38][39][40] we initiated a program to access the feasibility of reacting electron decient aldimines with o-haloanilines in the presence of a Pd catalyst in an effort to carry out a sequential Buchwald-Hartwig/imine arylation process to give tricylic chiral dibenzoaminopiperidines (or hydrogenated acridines) (Fig. 1), that can act as chiral tacrine analogues for acetylcholine esterase inhibition.…”
Section: Resultsmentioning
confidence: 99%